Culturally Based Religious Moderation Communication in Bagansiapiapi for Interfaith Harmony - Hotna Sari; Hasan Sazali; Faridah Faridah (FAKULTAS DAKWAH UIN SALATIGA, 2025)
This study explores religious moderation communication in fostering interreligious harmony in Bagansiapiapi, Rokan Hilir, Riau. It focuses on three aspects: (1) community understanding of religious moderation, (2) communication practices that support interfaith harmony, and (3) supporting and inhibiting factors in promoting religious coexistence. Using a qualitative approach, data were collected through field observation, interviews, and documentation involving religious leaders, community figures, local authorities, organizations, and multireligious communities. Findings reveal that religious moderation in Bagansiapiapi is deeply embedded in the local culture, with core values such as national commitment, tolerance, anti-violence, and acceptance of cultural diversity shaping daily interactions. Communication of religious moderation is practiced through inclusive and symbolic interactions based on Communication Accommodation Theory (CAT) and Symbolic Interactionism. Key enablers include inclusive cultural values, proactive community leadership, and empathy-driven communication. Challenges arise from the absence of permanent interfaith youth forums and limited institutional support. The novelty of this research lies in three contributions: (1) the formulation of a Cultural-Accommodative Communication Model, where symbolic convergence fosters organic interfaith engagement; (2) positioning religious moderation as a community-based collective identity rather than a top-down directive; and (3) demonstrating how religious and national symbols function as active instruments of moderation communication. These findings provide valuable insights for the development of sustainable religious harmony strategies in other multicultural settings.